Decade-long Trends in the Frequency of 90-day Rehospitalizations after Hospital Discharge for Acute Myocardial Infarction - Chen, Han-Yang (Am J Cardiol, 2015)
There are limited data available describing relatively contemporary trends in 90-day rehospitalizations among patients who survive hospitalization after an acute myocardial infarction (AMI) in a community setting. We examined decade-long (2001–2011) trends in, and factors associated with, 90-day rehospitalizations in patients discharged from three central Massachusetts (MA) hospitals after AMI. Residents of the Worcester, MA, metropolitan area discharged after AMI from three central MA hospitals on a biennial basis between 2001 and 2011 comprised the study population (n=4,810). The average age of this population was 69 years, 42% were women, and 92% were white. Between 2001 and 2011, 30.0% of patients were rehospitalized within 90 days after hospital discharge, and 38% of 90-day rehospitalizations occurred after the first month post hospital discharge. Crude 90-day rehospitalization rates decreased from 31.5% in 2001/2003 to 27.3% in 2009/2011. After adjusting for several sociodemographic characteristics, comorbidities, and in-hospital factors, there was a reduced risk of being rehospitalized within 90 days after hospital discharge in 2009/2011 compared with 2001/2003 (risk ratio (RR)=0.87, 95% confidence interval (CI)=0.77 to 0.98); this trend was slightly attenuated (RR=0.90, 95% CI=0.79 to 1.02) after further adjustment for hospital treatment practices. Female sex, having several previously diagnosed comorbidities, an increased hospital stay, and the in-hospital development of atrial fibrillation, cardiogenic shock, and heart failure were significantly associated with an increased risk of being rehospitalized. In conclusion, the likelihood of subsequent 90-day rehospitalizations remained frequent, and we did not observe a significant decline in these rates during the years under study.